ANALYSIS OF COVID-19 DISCHARGED CASES AND EQUITY TURNOVER IN THE NIGERIAN CAPITAL MARKET: AN EVENT STUDY APPROACH - Babarinde, Gbenga Festus (The International Journal of Accounting and Business Society, 2021)
Purpose —  The purpose of this study is to investigate the effect of cumulative and new discharged cases of COVID-19 on equity turnover value in the Nigerian Stock Exchange(NSE) between March 2, 2020, and September 25, 2020.Design/methodology/approach —  Correlation test and Vector Autoregressive (VAR) model were used to analyze the daily time series data sourced from the Nigerian Stock Exchange and the Nigeria Centre for Disease Control(NCDC) websites.Findings —  The study found evidence of a weak negative correlation between measures of COVID-19 recovery and equity turnover value in Nigeria. Furthermore, the VAR model results indicate that cumulative and new discharged cases of COVID-19 have a negative but non-significant impact on equity turnover value in Nigeria over the study periodPractical implications —  This implies that COVID-19 recovery cases still have the potential to shrink equity turnover value in the Nigerian capital market, though its influence may not be significant. There is therefore the need to speed up the vaccine development/commercial launch pace and other measures to curb the pandemic and ensure quicker recovery of those infected persons. These will help to reduce the long-run potential threat of COVID-19 on the Nigerian capital market. Originality/value —  This paper provides empirical evidence on the nexus between COVID-19 discharged cases and equity turnover in a developing economy, this is Nigeria. It is expected that this case will help the investment community particularly, the capital market investors on the potential influence of COVID-19 on market transactions in terms of turnover, such that the prolongation of the coronavirus pandemic constitutes an important source of financial volatility in the capital market of the country.Keywords —  Coronavirus; COVID-19; Discharge cases; Recovery rate; Equity turnover value; Nigerian Stock Exchange; Vector Autoregressive (VAR).Paper type —  Research Paper